Comparative Study on the Syntheses and Properties of Three N‐lauroyl Aromatic Amino Acid Surfactants. Issue 4 (1st April 2020) - Yang, Jian; Zhou, Yawen; Yang, Bo; Huang, Luyang; Liu, Changyao; Han, Fu; Xu, Baocai
Abstract: Three N‐lauroyl aromatic amino acid surfactants, namely, sodium N‐lauroyl phenylalaninate (SLP), sodium N‐lauroyl tyrosinate, and sodium N‐lauroyl tryptophanate (SLTr), with aromatic group structures were synthesized via methyl ester method. Mass spectrometry, Fourier transform infrared spectroscopy, and nuclear magnetic resonance were applied for the structural representation of products. A comparative study of the three surfactants in terms of surface, foam, and emulsifying properties and decontamination performance was conducted. Results demonstrated that aromatic structure significantly influenced the properties of the three surfactants. SLTr had the best surface performance and foam property, whereas SLP had the best emulsifying property. All three surfactants exhibited strong decontamination effects on protein‐soiled swatches.